Faktor-Faktor Psychological Well Being pada Remaja - Prihartini, Dela; Al Habsy, Bakhrudin; Hariastuti, Retno Tri; Christiana, Elisabeth (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
Psychological well being is a picture of an individual who has a balanced mental health so that he can fully update himself in the face of the challenges of his life. However, there are many factors that can influence a teenager in his developmental tasks to be able to update himself so he can develop the positive potential he has well. It can also affect the psychological well being of adolescents. The aim of this research is to find any factors that affect the psychological well being of adolescents. This research uses qualitative methods and kinds of literary study research. The results of the study show that there are 17 factors that can influence psychological well-being including life meaning, social support, forgiveness, evaluation of life experiences, locus of control, demographic, religiousness, lifestyle patterns, financial problems, relationships with others, dispositional mindfulness, emotional regulation, psychosocial, prosocial behavior, FOMO behaviour, self-esteem, and stress levels. So it can be concluded that these 17 factors can significantly affect psychological well being.